2023
DOI: 10.1007/s00117-023-01197-6
|View full text |Cite
|
Sign up to set email alerts
|

Femoroazetabuläres Impingement beim Jugendlichen und Adoleszenten

Iris-M. Noebauer-Huhmann,
Felix R. M. Koenig,
Catharina Chiari
et al.

Abstract: ZusammenfassungDas femoroazetabuläre Impingement-Syndrom (FAIS) wird durch einen repetitiven mechanischen Konflikt zwischen Azetabulum und proximalem Femur insbesondere bei Flexion und Innenrotation hervorgerufen. Beim femoroazetabulären Impingement (FAI) vom Cam-Typ bewirkt eine Asphärizität am femoralen Kopf-Hals-Übergang die Induktion von Scherkräften am Azetabulum. Beim Pincer-Typ kann eine Retroversion der Pfanne und/oder eine vermehrte Überdachung vorliegen. Ein wichtiger mechanischer Einflussfaktor, wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A low MPTA leads to compensatory internal rotation of the leg within the hip joint during flexion of the knee and hip. This would increase the risk of anterior femoroacetabular impingement (FAI), given the established association between reduced femoral torsion and anterior FAI [28]. In their recent study, Boschung et al successfully identified the areas of conflict around the hip joint in deep hip flexion for patients with reduced femoral torsion [1].…”
Section: Discussionmentioning
confidence: 99%
“…A low MPTA leads to compensatory internal rotation of the leg within the hip joint during flexion of the knee and hip. This would increase the risk of anterior femoroacetabular impingement (FAI), given the established association between reduced femoral torsion and anterior FAI [28]. In their recent study, Boschung et al successfully identified the areas of conflict around the hip joint in deep hip flexion for patients with reduced femoral torsion [1].…”
Section: Discussionmentioning
confidence: 99%